AN ANALYSIS OF THE INTENSITY OF REMEDIAL ACTIVITIES AND SELF-EFFICACY ON STUDENT LEARNING OUTCOMES: A MIXED-METHODS STUDY - Indang Wandhan Sari; Abdul Bashith; Umi Julaihah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the contribution of remedial activity intensity and self-efficacy to improving student learning outcomes. The method used is a mixed method, combining a quantitative approach to examine the relationships between variables and a qualitative approach through interviews and observations to strengthen field findings. The results indicate that consistent student engagement in remedial activities is associated with improved academic achievement. Remedial activities serve not only to improve grades but also as an opportunity for students to review the material until it is fully understood. Meanwhile, self-efficacy contributed to students' learning motivation, mental readiness, and courage to face academic challenges. These findings indicate that these two variables are important factors that mutually support learning success, so remedial implementation should be designed to strengthen understanding and foster students' learning confidence.